Outcome of two patients with bilateral nephroblastomatosis/Wilms tumour treated with an add-on 13-cis retinoic acid therapy – Case report. (20th November 2018) - Friesenbichler, Waltraud; Krizmanich, Wolfgang; Lakatos, Karoly; Attarbaschi, Andishe; Dworzak, Michael; Amann, Gabriele; Furtwängler, Rhoikos; Graf, Norbert; Kager, Leo
Abstract: Although the fate of nephrogenic rests varies, they are known to be precursors of Wilms tumour. Thus, nephrogenic rests require adequate treatment to prevent malignant transformation. We added 13-cis retinoic acid to the standard chemotherapy with vincristine and actinomycin-D in two patients with bilateral nephrogenic rests/nephroblastomatosis. Patient 1 also had a history of Wilms tumour. 46 (patient 1) and 81 (patient 2) months after end of treatment, both patients show stable conditions with no signs of relapse or progressive disease. Our observation supports further investigation of retinoic acid in patients with nephrogenic rests and nephroblastomatosis.